(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
This paper presents the geochemistry and geotechnical properties of some clays depos ited within sandstones of the Bima Formation in Girei and Environs. The aim is to under stand their economic potentials for the national development. The study area falls within latitudes 9°20’ N to 9°25’ N and Longitudes 12°30’ E to 12°34’ E with aerial extent of about 60 km2. Field work was carried out systematically in the study area whereby clay samples within the Bima Sandstone were collected for the purpose of laboratory analy sis. The X-ray fluorescence and geotechnical analysis carried out on the samples showed the average concentration of silica to be 69.55%, while iron oxide (4.5%) and low water absorption, low plasticity index, respectively. The concentration of the oxides suggests that the clays from the study area are unsuitable for refractory fired clays and production of high-grade ceramic materials; however, they can be used for burnt bricks and tradi tional ceramics production.